A transaction model for environmental resource dependent Cyber-Physical Systems - Zhu, Huang (Kansas State University, 2014)
Cyber-Physical Systems (CPSs) represent the next-generation systems characterized by strong coupling of computing, sensing, communication, and control technologies. They have the potential to transform our world with more intelligent and efficient systems, such as Smart Home, Intelligent Transportation System, Energy-Aware Building, Smart Power Grid, and Surgical Robot. A CPS is composed of a computational and a physical subsystem. The computational subsystem monitors, coordinates and controls operations of the physical subsystem to create desired physical effects, while the physical subsystem performs physical operations and gives feedback to the computational subsystem. This dissertation contributes to the research of CPSs by proposing a new transaction model for Environmental Resource Dependent Cyber-Physical Systems (ERDCPSs). The physical operations of such type of CPSs rely on environmental resources, and they are commonly seen in areas such as transportation and manufacturing. For example, an autonomous car views road segments as resources to make movements and a warehouse robot views storage spaces as resources to fetch and place goods. The operating environment of such CPSs, CPS Network, contains multiple CPS entities that share common environmental resources and interact with each other through usages of these resources. We model physical operations of an ERDCPS as a set of transactions of different types that achieve different goals, and each transaction consists of a sequence of actions. A transaction or an action may require environmental resources for its operations, and the usage of an environmental resource is precise in both time and space. Moreover, a successful execution of a transaction or an action requires exclusive access to certain resources. Transactions from different CPS entities of a CPS Network constitute a schedule. Since environmental resources are shared, transactions in the schedule may have conflicts in using these resources. A schedule must remain consistent to avoid unexpected consequences caused by resource usage conflicts between transactions. A two-phase commit algorithm is proposed to process transactions. In the pre-commit phase, a transaction is scheduled by reserving usage times of required resources, and potential conflicts are detected and resolved using different strategies, such as Win-Lose, Win-Win, and Transaction Preemption. Two general algorithms are presented to process transactions in the pre-commit phase for both centralized and distributed resource management environments. In the commit phase, a transaction is executed using reserved resources. An exception occurs when the real-time resource usage is different from what has been predicted. By doing internal and external check before a scheduled transaction is executed, exceptions can be detected and handled properly. A simulation platform (CPSNET) is developed to simulate the transaction model. The simulation platform simulates a CPS Network, where different CPS entities coordinate resource usages of their transactions through a Communication Network. Depending on the resource management environment, a Resource Server may exist in the CPS Network to manage resource usages of all CPS entities. The simulation platform is highly configurable and configuration of the simulation environment, CPS entities and two-phase commit algorithm are supported. Moreover, various statistical information and operation logs are provided to monitor and evaluate the platform itself and the transaction model. Seven groups of simulation experiments are carried out to verify the simulation platform and the transaction model. Simulation results show that the platform is capable of simulating a large load of CPS entities and transactions, and entities and components perform their functions correctly with respect to the processing of transactions. The two-phase commit algorithm is evaluated, and the results show that, compared with traditional cases where no conflict resolving is applied or a conflicting transaction is directly aborted, the proposed conflict resolving strategies improve the schedule productivity by allowing more transactions to be executed and the scheduling throughput by maintaining a higher concurrency level.
Keywords: Cyber-Physical Systems; Transaction Model; Environmental Resources; Two-Phase Commit; Conflict Resolving; CPSNET; Simulation; Computer Science (0984)